Pyoperitoneum associated with uterovaginal prolapse in two elderly women - Pradhan, N; Rana, A; Gurung, G; Zaffar, S (Journal of Institute of Medicine Nepal, 2008)
Case report: Incarcerated uterovaginal prolapse due to pelvic and peritoneal abscess (pyoperitoneum) which at initial laparotomy was insufficiently dealt due to plastered peritoneum and dense pelvic adhesion, just by means of peritoneal lavage alone in one case and subtotal hysterectomy in the other and were wisely operated at a later date, removing uterus and bilateral adnexal mass at abdominal hysterectomy and bilateral salphingo-oophorectomy or removal of prolapsed cervix, that included the safety of surgical procedure is highlighted. Key words : Pyoperitoneum, pelvic abscess, peritoneal lavage The full text of this paper is available at Journal of Institute of Medicine website